A kind of high-strength coated sand and its preparation method and application
By using high-strength coated sand prepared by using high-reactive polyphenol linear phenolic resin, the problem of low consolidation strength of existing coated sand is solved, forming a high-strength sand-proof overall structure, which significantly improves the shear strength and sand-proof effect.
Patent Information
- Application Number
- CN202310808417.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-03
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-07-03
AI Technical Summary
The existing coated sand cannot be consolidated into a whole between the particles, and the consolidation strength after injection into the formation is low, making it difficult to effectively prevent the proppant from flowing back and sand out of the formation.
High-strength coated sand is prepared by using high-reactive polyphenol linear phenolic resin. After injection into the formation, the coated sand forms a high-strength sand-proof overall structure through secondary curing to improve shear strength.
The shear strength of the coated sand after curing is significantly improved, forming a high-strength sand barrier, effectively preventing proppant from returning and sand from the formation, and improving the long-term diversion capacity of hydraulic fracturing construction.
Smart Images

Figure CN116904181B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil and gas reservoir reservoir transformation and oil reservoir sand control, and in particular to high-strength coated sand and a preparation method and application thereof. Background Art
[0002] Although conventional oil and gas resources are relatively easy to exploit, they only account for 20% of the world's total oil and gas resources, while unconventional oil and gas resources such as tight oil, tight gas, shale oil, and shale gas account for 80% of the world's total oil and gas resources. As conventional oil and gas gradually fail to meet the needs of exploitation, people's development strategies are gradually developing towards unconventional oil and gas. Unconventional oil and gas reservoirs have the characteristics of low porosity and low permeability, low reservoir permeability, and poor physical properties. Therefore, hydraulic fracturing is usually required. At present, hydraulic fracturing technology has become a necessary means for the efficient development of unconventional oil and gas reservoirs. Its purpose is to form a large-scale fracture network in unconventional oil and gas reservoirs and increase the fluid seepage volume. Proppant plays a key role in fracturing construction. In order to prevent the closure of newly opened cracks, sand-carrying fluid carrying proppant needs to be squeezed into the reservoir to support the already opened cracks and keep them open. At present, the commonly used proppants for hydraulic fracturing are quartz sand, ceramsite, and coated sand. Natural quartz sand is low-cost and is the most widely used in fracturing construction sites, but it has low compressive strength and a high crushing rate under formation pressure, which affects the long-term conductivity of the fracture. Ceramsite proppants have high compressive strength and good crack support effects, but the preparation process is complex and the cost is high, making it difficult to use on a large scale. Coating natural quartz sand can greatly improve the compressive strength of the sand particles, while wrapping the broken sand particles to prevent the broken sand particles from migrating and causing sand problems.
[0003] At the same time, for weakly cemented reservoirs, under fluid scouring, the reservoir sand body is prone to lose cement and produce sand, leading to formation collapse, wear of pumping pipes and related production equipment, and affecting the efficiency of crude oil production. Coated sand can effectively improve the stability of the sand body and slow down the sand production of weakly cemented reservoirs by connecting between particles.
[0004] Coated sand is divided into pre-cured coated sand and curable coated sand. Pre-cured coated sand is the mainstream coated sand currently used on site. It has been cured before being injected into the formation, but it only improves the strength of the particles themselves. The particles cannot be consolidated into a whole and cannot effectively prevent and block sand.
[0005] Since the coated sand currently has the disadvantages of being unable to consolidate into a whole between particles and having low consolidation strength, it is necessary to study a new type of high-strength curable coated sand for hydraulic fracturing and oil reservoir sand control. The quartz sand is coated. While further enhancing the compressive strength of the proppant, the proppant coating can further promote the solidification of the coated sand at the reservoir temperature to form a high-strength sand control overall structure aggregate, which plays a role in preventing the proppant from flowing back and preventing the formation from sanding. However, the actual operation of measuring the amount of sand produced during the strength test of the coated sand is difficult, and the amount of sand produced is difficult to measure accurately. In this experiment, the relationship between the amount of sand produced and the shear strength is first established. The shear strength is linearly correlated with the amount of sand produced. Therefore, the shear strength can be used instead of the sand production to evaluate the performance of the coated sand after solidification, and the predecessors have also used the shear strength as the evaluation standard of the coated sand. Therefore, the present invention provides a high-strength coated sand that can significantly improve the shear strength after the injection formation is solidified, improves the stability of the sand body, and effectively solves the problem of sand production. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems in the prior art that the coated sand particles cannot be consolidated into a whole and the consolidation strength is low after being injected into the formation, and to provide a high-strength coated sand and its preparation method and application. The high-strength coated sand is prepared by using a specific high-activity polyphenol linear phenolic resin, and the coated sand is loose particles. After the high-strength coated sand is injected into the formation and solidified, the coated sand particles can be solidified into an overall structure aggregate, and the coated sand can also be solidified as a whole with the formation surface, thereby forming a higher strength sand barrier in the near-well area, significantly improving the shear strength of the overall structure formed after solidification; and after the formed overall structure aggregate is compressed, the coated sand will not break into single-particle loose sand, and a relatively complete sand body can be maintained.
[0007] In order to achieve the above-mentioned purpose, the present invention provides a high-strength coated sand on one hand, wherein the high-strength coated sand is a loose particle prepared from raw materials containing raw sand, resin, toughening agent, curing agent and dispersant, wherein the resin is a high-activity polyphenol linear phenolic resin, and the weight ratio of the raw sand, the resin, the toughening agent, the curing agent and the dispersant is 100: 2-10: 0.04-2: 0.16-4: 0.14-0.7, preferably 100: 4-6: 0.48-0.72: 0.6-0.9: 0.28-0.42; wherein the high-activity polyphenol linear phenolic resin has a softening point of 50-120°C, preferably 70-100°C, and a molecular weight of 3000-7000;
[0008] The structure of the highly active polyphenol linear phenolic resin is shown in formula (1):
[0009]
[0010] Wherein, R1 and R2 are each independently selected from -OH or -CH3; and n is 5-14.
[0011] Preferably, the raw sand is selected from one or more of quartz sand, ceramsite, wood chips, nut shell chips and metal particles.
[0012] Preferably, the toughening agent is selected from one or more of dibutyl phthalate, dimethyl phthalate, dioctyl phthalate and aminosulfonic acid.
[0013] Preferably, the curing agent is selected from one or more of urotropine, triethylenetetramine, ethylenediamine, phenol, formaldehyde and acetone.
[0014] Preferably, the dispersant is calcium stearate.
[0015] Preferably, the high-activity polyphenol linear phenolic resin has a fluidity of 70-90% and a polymerization rate of 55-85s.
[0016] A second aspect of the present invention provides a method for preparing the high-strength coated sand as described above, the method comprising the following steps:
[0017] (1) continuously heating the sand mixer, adding raw sand into the sand mixer for stirring while maintaining the temperature of the sand mixer at T°C;
[0018] (2) When the temperature of the raw sand is T°C, the resin and toughening agent solution as shown in formula (1) are added in sequence;
[0019] (3) stopping heating the sand mixer, and then adding the curing agent aqueous solution into the sand mixer and stirring for 20-50 seconds;
[0020] (4) adding a dispersant into the sand mixer and stirring with cold air to obtain high-strength coated sand;
[0021] The T is calculated according to formula (2):
[0022] T = C + D Formula (2)
[0023] Wherein, T is the optimum temperature for resin coating, C is the softening point of the resin, D is the temperature margin, and the units of T, C and D are ℃.
[0024] Preferably, the T is 90-160°C, more preferably 110-140°C, further preferably 125°C.
[0025] Preferably, in step (1), before adding the raw sand into the sand mixer, the raw sand is first heated to 160-240° C. and maintained at this temperature for 8-15 minutes.
[0026] Preferably, in step (2), before adding the raw sand into the sand mixer, the sand mixer is preheated at T°C for 8-15 minutes.
[0027] Preferably, in step (1), the process of sequentially adding the resin and the toughening agent solution comprises: after adding the resin, stirring for 160-250 seconds, then adding the toughening agent solution, and stirring for 80-150 seconds.
[0028] Preferably, the concentration of the toughening agent solution is 20-30% by weight.
[0029] Preferably, the concentration of the aqueous curing agent solution is 25-35% by weight.
[0030] A third aspect of the present invention provides an application of the high-strength coated sand described above and the high-strength coated sand prepared by the method described above, and the application comprises: injecting the high-strength coated sand into a formation and then solidifying it.
[0031] Preferably, the amount of high-strength coated sand is 50-5000m 3 .
[0032] Preferably, the curing temperature is 80-160° C., and the curing time is 3-60 hours.
[0033] Compared with traditional single-particle loose sand particles, the high-strength coated sand provided by the present invention can greatly improve the reliability of proppant supporting cracks, and improve the problem of reduced seepage space caused by crack closure in the later stage of fracturing construction; and for weakly cemented and sand-prone reservoirs, the high-strength coated sand of the present invention can form a high-strength sand barrier in the near-well area after being injected into the formation, thereby achieving sand prevention.
[0034] The coated sand provided by the present invention facilitates its better application in the hydraulic fracturing construction of deep or even ultra-deep oil and gas fields and the sand control measures of loose sandstone reservoirs, so as to solve the problem that the proppant has a high crushing rate and sand production under high pressure, and is difficult to effectively support the cracks, protect the long-term conductivity of the hydraulic fracturing artificial cracks, and improve the hydraulic fracturing construction effect. In addition, the high-strength coated sand that can be consolidated can be solidified under the formation temperature and pressure conditions to form an overall structural aggregate, which plays the role of a sand barrier, effectively improves the construction effect of on-site sand control measures, prevents formation collapse, slows down the wear of the pumping pipe column and related production equipment, protects the reservoir, and ultimately improves the timeliness of crude oil production.
[0035] Compared with the prior art, the high-strength coated sand provided by the present invention has at least the following advantages:
[0036] Although the price of traditional quartz sand for fracturing is low, its compressive strength is low, and its crushing rate is high under the influence of formation pressure, which affects the long-term conductivity of the fracture; pre-cured coated sand is chemically plated outside the ordinary proppant, which can enhance the compressive strength of the basic sand particles, and only simply improves the strength of the particles themselves. The particles are still loose sand without force, and cannot play the role of sand prevention by cementing and blocking sand; the existing curable coated sand generally has the problem of low consolidation strength, and it is difficult to play a good supporting role in deep formations. The new curable coated sand prepared by the present invention has a higher shear strength of the aggregate formed after curing than the existing ordinary coated sand, and its preparation process is simple, the raw materials are easy to obtain, and it has a better supporting effect on the fracture under the same conditions; and the structural strength of the consolidated body formed after cementing is relatively high, and it will not break into loose sand like ordinary coated sand after being compressed, and only partial tensile cracks will be generated, maintaining a good consolidation structure and good permeability, and can also be used for the construction of chemical sand prevention measures for sand-prone reservoirs.
[0037] In summary, the high-strength coated sand provided by the present invention not only improves the compressive strength of the coated sand particles by coating means, but also realizes secondary consolidation under the formation temperature and pressure conditions after being injected into the formation, forming a high-strength sand-proof structure as a whole. When the stress exceeds the structural strength, cracks are generated, but the overall structure is still maintained, and the conductivity of the coated sand structure as a whole is effectively maintained. The coated sand can be used in the hydraulic fracturing process to improve the long-term conductivity of the cracks and the hydraulic fracturing construction effect by slowing down the sand production; it can also be used in formations prone to sand production to form an overall sand-proof structure through re-consolidation, effectively improving the sand production problem of loose sandstone oil and gas reservoirs, and slowing down the backflow of coated sand, protecting the reservoir, and stabilizing the production of oil and gas wells. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 is a schematic diagram of a high-strength coated sand product prepared in Example 1;
[0039] Figure 2 This is a rupture diagram of a high-strength overall structure aggregate formed by injecting high-strength coated sand into the formation under pressure in Example 1;
[0040] Figure 3 It is a schematic diagram of the on-site application of the fracturing process. DETAILED DESCRIPTION
[0041] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0042] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0043] On one hand, the present invention provides a high-strength coated sand, which is a loose particle prepared from raw materials containing raw sand, resin, toughening agent, curing agent and dispersant, and the resin is a high-activity polyphenol linear phenolic resin.
[0044] The high-strength coated sand provided by the present invention is prepared by using a specific high-activity polyphenol linear phenolic resin, and the high-strength coated sand is in the form of loose particles, and the high-strength coated sand can be injected into the formation to solidify and form a consolidated structure with high shear strength. When used, the high-strength coated sand can be injected into the formation alone or together with other proppant components.
[0045] In a specific embodiment, the weight ratio of the raw sand, the resin, the toughening agent, the curing agent and the dispersant can be 100:2-10:0.04-2:0.16-4:0.14-0.7.
[0046] In a preferred embodiment, in order to improve the shear strength of high-strength coated sand after injection into the formation and solidification, the weight ratio of the raw sand, the resin, the toughening agent, the curing agent and the dispersant is 100:4-6:0.48-0.72:0.6-0.9:0.28-0.42.
[0047] The high-activity polyphenol linear phenolic resin used in the present invention is different from conventional thermoplastic phenolic resin. On the one hand, the molecular structure of the high-activity polyphenol linear phenolic resin used in the present invention is different. The reaction activity of ordinary thermoplastic phenolic resin is relatively low, mainly because the para position with higher reaction activity on the phenol ring is replaced by the reaction substance, resulting in reduced reaction activity; the high-activity polyphenol linear phenolic resin used in the present invention is designed through molecular structure, and the adjusted phenolic resin for oilfield sand control agent is mainly a linear phenolic resin with an ortho structure as the main structure, retaining the para position with high reaction activity of the phenol ring, and maintaining the reaction activity of the phenolic resin higher than that of ordinary thermoplastic phenolic resin.
[0048] In the present invention, the high-activity polyphenol linear phenolic resin has a softening point of 50-120°C, preferably 70-100°C, and a molecular weight of 3000-7000. The softening point of the resin is tested by the ring and ball method, and the temperature at which the heated and molten resin or steel ball begins to contact the lower metal plate is the softening point temperature.
[0049] According to the present invention, the structure of the highly active polyphenol linear phenolic resin is shown in formula (1):
[0050]
[0051] Wherein, R1 and R2 are each independently selected from -OH or -CH3; and n is 5-14.
[0052] The high-activity polyphenol linear phenolic resin of the invention is a light yellow semi-transparent liquid or semi-solid, with a fluidity of 70-90% and a polymerization speed of 55-85s.
[0053] In the present invention, the method for determining the fluidity of the resin is as follows: a sample is cut from the resin sample and placed in a sample assembly composed of a glass cloth for absorbing glue and a separator, and the sample assembly is placed in a flat press at a temperature of 100°C and a pressure of 600 kPa for curing. After curing, part of the resin flows out of the sample. The percentage change in mass of the sample before and after the test is the fluidity of the resin.
[0054] In the present invention, the method for determining the polymerization rate is: first place a scraper on a hot plate for preheating, then weigh 1.0g (accurate to 0.01g) of the sample, and use a scraper to evenly distribute it in a central groove with a diameter of 50mm on a polymerization hot plate preheated to 100°C, and then press the stopwatch after placing the sample to start timing. Use the scraper to draw a wire from left to right and then from right to left upward until no wire can be drawn, then stop timing immediately, and record the time used as the polymerization time of the resin.
[0055] In a specific embodiment, the raw sand is selected from one or more of quartz sand, ceramsite, wood chips, nut shell chips and metal particles, and may also be other debris particles; preferably, it is quartz sand.
[0056] In a specific embodiment, the toughening agent is selected from one or more of dibutyl phthalate, dimethyl phthalate, dioctyl phthalate and aminosulfonic acid. In a preferred embodiment, in order to further improve the strength of the prepared coated sand and reduce the amount of sand produced, the toughening agent is dioctyl phthalate.
[0057] In a specific embodiment, the curing agent is selected from one or more of urotropine, triethylenetetramine, ethylenediamine, phenol, formaldehyde and acetone; preferably urotropine.
[0058] In a specific embodiment, the dispersant may be calcium stearate.
[0059] A second aspect of the present invention provides a method for producing high-strength coated sand as described above, the method comprising the following steps:
[0060] (1) Continuously heating the sand mixer, adding raw sand into the sand mixer for stirring while the temperature of the sand mixer is maintained at T°C; (2) When the temperature of the raw sand is T°C, adding the resin and toughening agent solution shown in formula (1) in sequence; (3) Stop heating the sand mixer, then add the curing agent aqueous solution into the sand mixer and stir for 20-50s; (4) Add the dispersant into the sand mixer and stir with cold air to obtain high-strength coated sand; T is calculated according to formula (2):
[0061] T = C + D Formula (2)
[0062] Wherein, T is the optimum temperature for resin coating, C is the softening point of the resin, and D is the temperature margin. The units of T, C and D are °C. In the present invention, the optimum temperature for resin coating refers to the temperature at which the viscosity of the resin drops to a temperature suitable for coating the raw sand. If the temperature is lower than its softening point, the resin does not have the ability to consolidate. If the temperature is too high, the resin molecules may lose stability and damage their reconsolidation performance. In the present invention, the temperature margin is the difference between the optimum temperature for resin coating and the softening point of the resin.
[0063] In the method described in the present invention, the inventors have found that only by limiting T within a suitable range can the resin and toughening agent be better coated outside the original sand, thereby improving the shear resistance of the coated sand after being injected into the formation and solidified.
[0064] In a preferred embodiment, the T may be 90-160° C., such as 90° C., 100° C., 110° C., 120° C., 130° C., 140° C., 150° C. or 160° C. In a more preferred embodiment, the T is 110-140° C., and in a most preferred embodiment, the T is 125° C.
[0065] In the method of the present invention, in step (1), in order to heat the raw sand to a temperature at which the resin can be melted, the raw sand can be heated to a temperature higher than T before being added to the sand mixer. In a specific embodiment, in step (1), before being added to the sand mixer, the raw sand can be heated to 160-240° C., such as 160° C., 180° C., 200° C., 220° C. or 240° C.; and maintained for 8-15 min, such as 8 min, 10 min, 12 min, 14 min or 15 min.
[0066] In the method of the present invention, the coating preparation process of the sand is not completed instantly, but requires a period of time. During this period of time, the preparation environment needs to maintain a certain temperature, and the heating of the sand mixer is to maintain this temperature. Therefore, in step (2), before adding the raw sand to the sand mixer, the sand mixer can be preheated at T℃ for 8-15 minutes, such as 8 minutes, 10 minutes, 12 minutes, 14 minutes or 15 minutes.
[0067] In the method of the present invention, the toughening agent needs to be dissolved in ethanol to form a toughening agent solution for use. In a specific embodiment, the concentration of the toughening agent solution can be 20-30% by weight, such as 20% by weight, 22% by weight, 25% by weight, 26% by weight, 28% by weight or 30% by weight.
[0068] In a specific embodiment, in step (1), the process of sequentially adding the resin and the toughening agent solution includes: after adding the resin, stirring for 160-250s, such as 160s, 180s, 200s, 220s or 250s, and then adding the toughening agent solution and stirring for 80-150s, such as 80s, 100s, 120s, 140s or 150s.
[0069] In the method of the present invention, the curing agent needs to be diluted into an aqueous solution before use. In a specific embodiment, the concentration of the curing agent aqueous solution is 25-35% by weight, such as 25% by weight, 30% by weight or 35% by weight.
[0070] In the method of the present invention, in order to obtain high-strength coated sand of bulk particles and significantly improve the shear strength of the high-strength coated sand at the formation temperature after being injected into the formation, it is necessary to reasonably control the amount of curing agent and the stirring time after the curing agent is added to the sand mixer. In a specific embodiment, the stirring time of adding the curing agent aqueous solution to the sand mixer can be 20-50s, such as 20s, 25s, 30s, 35s, 40s, 45s or 50s.
[0071] A third aspect of the present invention provides an application of the high-strength coated sand described above prepared by the method described above, the application comprising: injecting the high-strength coated sand into a formation and then solidifying it.
[0072] In the present invention, the amount of high-strength coated sand can be adjusted according to the crack volume, construction requirements and design. In a specific embodiment, the amount of high-strength coated sand can be 50-5000m 3 .
[0073] In a preferred embodiment, the curing temperature can be 80-160°C, for example 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C or 160°C; the curing time can be 3-60h, for example 3h, 12h, 24h, 30h, 36h, 48h, 56h or 60h.
[0074] The present invention will be described in detail below by way of examples, but the protection scope of the present invention is not limited thereto. Unless otherwise specified, the reagents used in the examples of the present invention are all commercially available.
[0075] The structure of the highly active polyphenol linear phenolic resin used in the embodiment is shown in formula (1):
[0076]
[0077] Among them, R1 is -OH, R2 is -CH3; n is 5-14; the softening point is 85°C, the molecular weight is 3000-7000, the fluidity is 80%, and the polymerization rate is 70s.
[0078] Example 1
[0079] The preparation process of high-strength coated sand A1 is as follows:
[0080] (1) Take 5 kg of quartz sand and heat it to 200°C for 10 minutes; and preheat the sand mixer to 125°C for 10 minutes;
[0081] (2) transferring the hot sand to a continuously heated sand mixer for stirring, and when the temperature of the hot sand drops to 125° C., adding 100 g of highly active polyphenol linear phenolic resin and stirring for 200 s to obtain resin-coated sand particles;
[0082] (3) 12 g of dioctyl phthalate was diluted with ethanol to a 25 wt% solution, and the solution was added to a sand mixer and stirred for 120 s;
[0083] (4) Stop heating the sand mixer, take 15 g of urotropine diluted to a 30 wt % aqueous solution, add it to the sand mixer and stir for 30 seconds;
[0084] (5) Add 7 g of calcium stearate to a sand mixer, turn on the cold air, and stir vigorously until it becomes loose sand to obtain high-strength coated sand A1.
[0085] High-strength coated sand A1 is shown in the figure. Figure 1 It can be seen that the obtained coated sand is loose particles.
[0086] The solidification process of high-strength coated sand A1 injected into the formation is as follows:
[0087] The high-strength coated sand A1 was injected into a specific formation model and placed under pressure for 12 hours at a formation temperature of 120°C to solidify the sand body composed of the high-strength coated sand. The amount of high-strength coated sand A1 was 1000 cm 3 .
[0088] Depend on Figure 2 It can be seen that after solidification, the overall structure did not break into powder after being compressed, but only some new channels were formed, indicating that the overall strength of the sand control structure formed by re-consolidation is relatively high.
[0089] According to the test, the sand output of the overall structure aggregate obtained after curing is 14.68g.
[0090] Example 2
[0091] The preparation process of high-strength coated sand A2 is as follows:
[0092] (1) Take 5 kg of quartz sand and heat it to 200°C for 10 minutes; and preheat the sand mixer to 130°C for 10 minutes;
[0093] (2) transferring the hot sand to a continuously heated sand mixer for stirring, and when the temperature of the hot sand drops to 130° C., adding 250 g of highly active polyphenol linear phenolic resin and stirring for 200 s to obtain resin-coated sand particles;
[0094] (3) Take 30 g of dioctyl phthalate and dilute it with ethanol to a 25 wt% solution, add it into a sand mixer and continue stirring for 120 seconds;
[0095] (4) Stop heating the sand mixer, take 37.5 g of urotropine diluted to a 30 wt % aqueous solution, add and stir for 30 s;
[0096] (5) Add 17.5 g of calcium stearate into a sand mixer, turn on the cold air, and stir vigorously until it becomes loose sand to obtain high-strength coated sand A2.
[0097] The solidification process of high-strength coated sand A2 injected into the formation is as follows:
[0098] The high-strength coated sand A2 was injected into a specific formation model and placed under pressure for 12 hours at a formation temperature of 120°C to solidify the sand body composed of the high-strength coated sand. The amount of high-strength coated sand A2 was 1000 cm 3 .
[0099] According to the test, the sand output of the overall structure aggregate obtained after curing is 3.86g.
[0100] Example 3
[0101] The preparation process of high-strength coated sand A3 is as follows:
[0102] (1) Take 5 kg of quartz sand and heat it to 200°C for 10 minutes; and preheat the sand mixer to 130°C for 10 minutes;
[0103] (2) transferring the hot sand to a continuously heated sand mixer for stirring, and when the temperature of the hot sand drops to 130° C., adding 250 g of highly active polyphenol linear phenolic resin and stirring for 200 s to obtain resin-coated sand particles;
[0104] (3) Take 30 g of dioctyl phthalate and dilute it with ethanol to a 25 wt% solution, add it into a sand mixer and continue stirring for 120 seconds;
[0105] (4) Stop heating the sand mixer, take 37.5 g of urotropine diluted to a 30 wt % aqueous solution, add and stir for 30 s;
[0106] (5) Add 17.5 g of calcium stearate into a sand mixer, turn on the cold air, and stir vigorously until it becomes loose sand to obtain high-strength coated sand A3.
[0107] The solidification process of high-strength coated sand A3 injected into the formation is as follows:
[0108] The high-strength coated sand A3 was injected into a specific formation model and placed under pressure for 48 hours at a formation temperature of 120°C to solidify the sand body composed of the high-strength coated sand. The amount of high-strength coated sand A3 was 1000 cm 3 .
[0109] According to the test, the sand output of the overall structure aggregate obtained after curing is 0.95g.
[0110] Comparative Example 1
[0111] The method of Example 2 was followed, except that common thermoplastic phenolic resin (epoxy resin H3) was used instead of high-activity polyphenol linear phenolic resin.
[0112] According to the test, the sand output of the overall structure aggregate obtained after curing is 56.13g.
[0113] Comparative Example 2
[0114] The method of Example 2 was followed, except that in step (2), 50 g of high-activity polyphenol linear phenolic resin was added, and the weight ratio of raw sand to resin was 100:1.
[0115] According to the test, the sand output of the overall structure aggregate obtained after curing is 29.33g.
[0116] It can be seen from the results of the embodiments and comparative examples that the sand output of the overall structure aggregate obtained after solidification of the high-strength coated sand obtained according to the technical solution of the present invention is significantly reduced.
[0117] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A high-strength coated sand, characterized in that: The high-strength coated sand is a loose particle prepared from raw materials containing raw sand, resin, toughening agent, curing agent and dispersant, the resin is a highly active polyphenol linear phenolic resin, and the weight ratio of the raw sand, the resin, the toughening agent, the curing agent and the dispersant is 100: 2-10: 0.04-2: 0.16-4: 0.14-0.7; The high-activity polyphenol linear phenol-formaldehyde resin has a softening point of 50-120° C., a molecular weight of 3000-7000, a fluidity of 70-90%, and a polymerization rate of 55-85 s. The structure of the highly active polyphenol linear phenolic resin is shown in formula (1): wherein R1 and R2 are each independently selected from -OH or -CH3; n is 5-14; The raw sand is selected from one or more of quartz sand, ceramsite, wood chips, nut shell chips and metal particles; The toughening agent is selected from one or more of dibutyl phthalate, dimethyl phthalate, dioctyl phthalate and aminosulfonic acid; The curing agent is selected from one or more of urotropine, triethylenetetramine, ethylenediamine and phenol; The dispersant is calcium stearate.
2. The high-strength coated sand according to claim 1, characterized in that: The softening point of the high-activity polyphenol linear phenolic resin is 70-100°C.
3. A method for preparing the high-strength coated sand according to claim 1 or 2, characterized in that: The method comprises the following steps: (1) continuously heating the sand mixer, adding raw sand into the sand mixer for stirring while maintaining the temperature of the sand mixer at T°C; (2) When the temperature of the raw sand is T°C, the resin and toughening agent solution as shown in formula (1) are added in sequence; (3) stopping heating the sand mixer, and then adding the curing agent aqueous solution into the sand mixer and stirring for 20-50 seconds; (4) adding a dispersant into the sand mixer and stirring with cold air to obtain high-strength coated sand; The T is calculated according to formula (2): T = C + D Formula (2) Wherein, T is the optimum temperature for resin coating, C is the softening point of the resin, D is the temperature margin, and the units of T, C and D are ℃.
4. The method according to claim 3, characterized in that The T is 90-160°C.
5. The method according to claim 4, characterized in that The T is 110-140°C.
6. The method according to claim 5, characterized in that The T is 125°C.
7. The method according to claim 3 or 4, characterized in that: In step (1), before adding the raw sand into the sand mixer, the raw sand is first heated to 160-240° C. and maintained at this temperature for 8-15 minutes.
8. The method according to claim 3 or 4, characterized in that: In step (2), before adding the raw sand into the sand mixer, the sand mixer is preheated at T°C for 8-15 minutes.
9. The method according to claim 3, characterized in that: In step (2), the process of sequentially adding the resin and the toughening agent solution includes: after adding the resin, stirring for 160-250 seconds, then adding the toughening agent solution, and stirring for 80-150 seconds.
10. The method according to claim 3, characterized in that The concentration of the toughening agent solution is 20-30% by weight.
11. The method according to claim 3, characterized in that The concentration of the curing agent aqueous solution is 25-35% by weight.
12. An application of the high-strength coated sand according to claim 1 or 2 and the high-strength coated sand prepared by the method according to any one of claims 3 to 11, characterized in that: The application includes: injecting the high-strength coated sand into a formation and then solidifying it.
13. The use according to claim 12, characterized in that: The amount of high-strength coated sand is 50-5000m 3 .
14. The use according to claim 13, characterized in that The curing temperature is 80-160° C., and the curing time is 3-60 hours.
Citation Information
Patent Citations
Manufacturing method for phenolic novolac resin and resin-coated sand
CN102066445A
Phenolic resin and preparation method thereof as well as proppant and preparation method thereof
CN102432786A
Cited By
Resin-coated quartz sand for fracturing and preparation method thereof
CN119752434A